2018
DOI: 10.1007/s00228-018-2416-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of phloroglucinol for treatment of abdominal pain: a systematic review of literature and meta-analysis of randomised controlled trials versus placebo

Abstract: There is insufficient data to justify the wide-spread prescription of phloroglucinol for alleviating abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Our mutation confirmed that the KR domain affects some polyketide chain-length. In particular, the replacement of Lys 1829 with Asp residue in ChrA KR afforded an remarkably escalated level of 2′,4′,6′-trihydroxyacetophenone ( 14 ), an anti-obesity phytochemical60 that serves as a (bio)synthetic starter motif for arrays of bioactive phloroglucinols 61,62. More interestingly, when ChrA KR and ChrB both lose the catalytic activity, the fungal chromane biosynthetic pathway constructs 13 that tends to form noreugenin ( 8 ), a plant chromone used as a common starting material for the synthesis of bioactive chromone natural products such as ptaeroxylin and eranthin 63.…”
Section: Discussionmentioning
confidence: 99%
“…Our mutation confirmed that the KR domain affects some polyketide chain-length. In particular, the replacement of Lys 1829 with Asp residue in ChrA KR afforded an remarkably escalated level of 2′,4′,6′-trihydroxyacetophenone ( 14 ), an anti-obesity phytochemical60 that serves as a (bio)synthetic starter motif for arrays of bioactive phloroglucinols 61,62. More interestingly, when ChrA KR and ChrB both lose the catalytic activity, the fungal chromane biosynthetic pathway constructs 13 that tends to form noreugenin ( 8 ), a plant chromone used as a common starting material for the synthesis of bioactive chromone natural products such as ptaeroxylin and eranthin 63.…”
Section: Discussionmentioning
confidence: 99%
“…Application of phloroglucinol during pregnancy does not increase the risk of fetal malformations [33]. It was applied to relieve renal colic and inhibit uterine contractions for decades [34,35]. Our research showed that application of phloroglucinol after ureteroscopy could reduce the incidence of uterine contractions.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, we did not find antispasmodic effects of phloroglucinol in bladder, while other report described very weak inhibition of phloroglucinol on normal intestinal peristalsis under spasms (Cahen, 1962). More recently, a meta-analysis of clinical reports concluded that only one randomized clinical trial found that phloroglucinol was superior to placebo treating abdominal pain, and that there is insufficient data to justify the wide-spread prescription of phloroglucinol (Blanchard et al, 2018). Moreover, there are medicines with anticholinergic and calcium antagonist properties to synergistically reduce the anormal contractions of bladder due to inestability or hiperactivity of detrusor (Sugaya et al 2012).…”
Section: Discussionmentioning
confidence: 99%